Digest: White‐eye birds provide possible answer to the paradox of the great speciator*. (12th August 2019) - Ottenburghs, Jente
Abstract: When organisms colonize a new area, they can come into secondary contact with closely related species. Consequent hybridization can lead to homogenizing gene flow and prevent genetic divergence. However, some lineages, like the White‐eye birds examined in this study, can speciate rapidly while colonizing a wide geographic area. The authors suggest that this "paradox of the great speciator" may be solved through unusually rapid evolution of reproductive isolation.